Spatio-Temporal Evolution of Intermediate-Depth Seismicity Beneath the Himalayas: Implications for Metamorphism and Tectonics - Michailos, Konstantinos; Carpenter, N. Seth; Hetényi, György (Frontiers in Earth Science, 2021)
Intermediate-depth earthquakes (>40 km) have been observed beneath the central Himalayas over decades, with little known about their nature and characteristics. Here, we apply a state- of-the-art, systematic processing routine, starting from continuous waveform data, to obtain the most comprehensive, high-quality earthquake catalog with a focus on the intermediate- depth seismicity beneath the central Himalayas. We construct a catalog containing 414 robust earthquake locations with depths ranging from 40 to 110 km spanning from late 2001 till mid-2003. We calculate earthquake magnitudes in a consistent way and obtain values ranging between M L 0.8 and 4.5 with a magnitude of completeness of M c 2.4. This information allows us to study the spatiotemporal characteristics of the seismicity in great detail. Earthquakes mainly take place in a cluster, consisting of two linear segments at ca. 35 ◦ azimuth difference, situated beneath the high Himalayas in NE Nepal and adjacent S. Tibet. Seismicity there does not feature any mainshock-aftershock patterns but presents a few sequences with potential seismicity migration rates compatible with linear or diffusive migration. This result along with previous studies in the lower Indian crust allows interpreting these events as related to metamorphic reactions involving dehydration processes. However, given the geodynamic context, a tectonic interpretation with a dextral basement fault zone propagating beneath the Himalaya and continuing as a westward propagating tear fault would also be possible. This represents a continuous fault zone from the deep crust in S. Tibet, across the Himalaya along the Dhubri-Chungthang fault zone (DCFZ) to the Shillong plateau, which could be an inherited tectonic feature.